Role of cardiac MRI in acute myocardial infarction (Medical Journal of Indonesia, 2013)
Mortality in patients with acute myocardial infarction (AMI) has decreased significantly and appears to be the result of current reperfusion therapeutic strategies. Reperfusion itself may develop into reperfusion injury. Therefore, management of these patients poses several challenges, such as diagnosing and managing heart failure, identifying persistent or inducible ischaemia, estimating the need for anticoagulation, and assessing overall cardiovascular risk. This case presentation will demonstrate the impact of cardiac magnetic resonance imaging (MRI) in the assessment of the pathophysiology of AMI in the current reperfusion era. Cardiac MRI can provide a wide range of clinically useful information which will help clinicians to manage and choose specific therapeutic strategies for AMI patients. (Med J Indones. 2013;22:46-53) Keywords: Acute myocardial infarction, cardiac magnetic resonance imaging, reperfusion injury